2010
DOI: 10.1002/anie.200905970
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Bis(σ‐BH) Aminoborane Complexes from Dehydrogenation of Amine–Boranes: Trapping of H2BNH2

Abstract: One small step for ammonia–borane: The simplest elementary aminoborane compound H2BNH2, which results from dehydrogenation of ammonia–borane, has been trapped by a ruthenium complex fragment leading to the isolation of a bis(σ‐BH) aminoborane complex. The analogous H2BNHMe and H2BNMe2 complexes were also prepared. (Picture: ruthenium complex; Ru purple, P orange, N blue, B brown, H white.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(30 citation statements)
references
References 51 publications
1
27
0
2
Order By: Relevance
“…However,t he 1 HNMR study of D at room temperature in a [ D 8 ]THF solution revealed the magnetic nonequivalence of the terminal hydrides (d = À11.94, À12.27 ppm). [9] This feature wasn ot observed in the case of the previously reportedc omplex [RuH 2 ((h 2 :h 2 -H 2 BNHMe)(PCy 3 ) 2 ] [6] with two different substituents attached to the terminal nitrogen atom. This difference is presumably because of aw eakb arrier to rotationa roundt he BÀNb ond, rendering the hydrogena toms surrounding the ruthenium center equivalent.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…However,t he 1 HNMR study of D at room temperature in a [ D 8 ]THF solution revealed the magnetic nonequivalence of the terminal hydrides (d = À11.94, À12.27 ppm). [9] This feature wasn ot observed in the case of the previously reportedc omplex [RuH 2 ((h 2 :h 2 -H 2 BNHMe)(PCy 3 ) 2 ] [6] with two different substituents attached to the terminal nitrogen atom. This difference is presumably because of aw eakb arrier to rotationa roundt he BÀNb ond, rendering the hydrogena toms surrounding the ruthenium center equivalent.…”
Section: Resultsmentioning
confidence: 81%
“…[5] Threey ears later,w er eportedt hat the bis(dihydrogen) complex [RuH 2 (h 2 -H 2 ) 2 (PCy 3 ) 2 ]( I) ( Figure 1) led to the stoichiometric dehydrogenation of amine-boranes H 3 BÀNMe 3Àn H n (n = 1-3), at room temperature, with formation of the corresponding bis-s-BÀHa minoborane rutheniumc omplexes [RuH 2 (h 2 :h 2 - ( Figure 1). [6] We clearly showed 1) the ability of ruthenium to retain the BÀNu nit along the elementarys teps of the amine-boraned ehydrogenation pathways, and 2) the bis-s-BÀHc oordination mode to be au seful tool for the stabilization of monomeric aminoboranes in the coordination sphere of the metal, [7] enabling even the trapping of the simplest and elusive prototypicalH 2 BÀNH 2 elementary unit ( Figure 1). [1a, 6] As ap art of our research programf ocusing on BÀHbond activation,w ew ere interestedt of urther explore the reactivity of the bis-s-BÀHc oordination mode, based on an approach reminiscentoft he intramolecular heterolytic cleavagep rocess of H 2 taking place in the first coordination sphere of am etal in the presenceo fanucleophile.…”
Section: Introductionmentioning
confidence: 99%
“…Unlängst berichteten wir sowohl über einen katalysatorfreien Reaktionsweg als auch über die Synthese des ersten hochmolekularen Poly(alkylphosphanylborans). [7] Eine ähnliche h 2 :h 2 -Koordination von [R 2 N=BH 2 ]w urde an einem Ir-Komplex beobachtet. ¾hnliche hochreaktive Verbindungen wie [H 2 N = BH 2 ] konnten unter kryogenen Bedingungen isoliert werden.…”
Section: Polymeredie Auf Hauptgruppenelementen Anstelle Vonunclassified
“…[4] These materials are prepared by transition-metal-catalyzed (Fe, [4b] Ir, [4d] Rh) [4a,c] dehydrocouplings of phosphine-borane adducts RPH 2 -BH 3 (R = Ph, iBu, p-nBuC 6 H 4 , p-C 12 H 25 C 6 H 4 ). [7] Thesame h 2 :h 2 coordination of [R 2 N=BH 2 ]w as observed within an Ir complex. [5] Thermal treatment of tBuPHBH 2 -NMe 3 leads to the elimination of NMe 3 and head-to-tail polymerization of the reactive intermediate [tBuPHBH 2 ], yielding [tBuPHBH 2 ] n .…”
mentioning
confidence: 93%